The Effect of Bonus Plan, Cash Holding and Leverage on Income Smoothing - Jannah, Kholifatul; Widiyati, Dian (International Journal of Social and Management Studies, 2023)
This research aims to prove empirically the effect of interest variable bonus plan, cash holding and leverage on income smoothing. This research was conducted in a manufacturing company in the consumer goods industry sector. The type of research used in quantitative with associative method. The type of data used is secondary data in the form of financial statement published on the Indonesia Stock Exchange (IDX) in 2016 – 2020. The sample was collected using the purpose sampling method. The number of companies that were used as research samples were 6 companies with research period of 5 years so that 30 observation data were obtained. The data was processed using the E-views 10 Statistical Program to test the hypothesis using panel data regression analysis. The result of the t statistical test show that of partially, cash holding and leverage influences income smoothing, while bonus plan has no effect on income smoothing. The result of the f statistical proves that the proportion bonus plan, cash holding and leverage simultaneously affect the income smoothing.